Implication of NADPH Oxidases in the Early Inflammation Process Generated by Cystic Fibrosis Cells. (5th July 2012) - Pongnimitprasert, Nushjira; Hurtado, Margarita; Lamari, Foudil; El Benna, Jamel; Dupuy, Corinne; Fay, Michèle; Foglietti, Marie-José; Bernard, Maguy; Gougerot-Pocidalo, Marie-Anne; Braut-Boucher, Françoise
Abstract : In cystic fibrosis (CF) patients, pulmonary inflammation is a major cause of morbidity and mortality. The aim of this study was to further investigate whether oxidative stress could be involved in the early inflammatory process associated with CF pathogenesis. We used a model of CFTR defective epithelial cell line (IB3-1) and its reconstituted CFTR control (S9) cell line cultured in various ionic conditions. This study showed that IB3-1 and S9 cells expressed the NADPH oxidases (NOXs) DUOX1/2 and NOX2 at the same level. Nevertheless, several parameters participating in oxidative stress (increased ROS production and apoptosis, decreased total thiol content) were observed in IB3-1 cells cultured in hypertonic environment as compared to S9 cells and were inhibited by diphenyleneiodonium (DPI), a well-known inhibitor of NOXs; besides, increased production of the proinflammatory cytokines IL-6 and IL-8 by IB3-1 cells was also inhibited by DPI as compared to S9 cells. Furthermore, calcium ionophore (A23187), which upregulates DUOX and NOX2 activities, strongly induced oxidative stress and IL-8 and IL-6 overexpression in IB3-1 cells. All these events were suppressed by DPI, supporting the involvement of NOXs in the oxidative stress, which can upregulate proinflammatory cytokine production by the airway CFTR-deficient cells and trigger early pulmonary inflammation in CF patients.